DAUN PEGAGAN (Centella asiatica) DAN KANGKUNG (Ipomea aquatica) SEBAGAI FOTOSENSITIZER PADA DYE SENSITIZED SOLAR CELL (DSSC) - Nening Listari (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2019)
Dye Sensitized Solar Cells (DSSCs) can use two types of coloring, namely dyes derived from organic and inorganic materials. The choice of natural dyes is preferred by looking at the enormous potential of biodiversity in Indonesia, where there are still many untapped especially for plants that have a tendency to be colored or contain chromophore dyes such as chlorophyll (play a role in the absorption of light for photosynthesis). The purpose of this study is to find out about the flow and efficiency of the natural dyes of the gotu kola leaves (Centella asiatica) and water spinach (Ipomea aquatica) on the island of Lombok where their wavelength characteristics are in the UV-Vis region. The technique used when coating TiO2 on the semiconductor glass is that DSSC is a doctor blade technique. In the measurement of current strength and efficiency with multimeters on organic dyes in a row that is 5 μA / cm2 fresh bebele leaves; 0.156; fresh kangkung leaves 4.2 μA / cm2; 0,131; 4 μA / cm2 dried bebele leaves; 0.13; dried kale leaf 3 μA / cm2; 0.088.